Developing mathematics virtual reality based on understanding mathematical concepts - Anisa, Putri Mutiara; Saenih, Saenih; Oktaviani, Anisa; Pramuditya, Surya Amami; Sundawan, Mohammad Dadan (Jurnal Elemen, 2024)
This research was motivated by students' difficulties understanding the basic concepts of abstract flat-side spatial shapes. So, learning media is needed to help students understand the material that is made interesting by utilising technology in the form of virtual reality. The research aims to determine the development of virtual reality media towards students' conceptual understanding, which has been tested validly and practically, so that it can be used as an active and exciting learning media. The method used in this research is a qualitative approach using the Research and Development method and the ADDIE model using the Millealab application. Participants were eighth-grade students at junior high schools. The outcomes of the research show that virtual reality is an innovative learning media that utilises technological developments in learning media and provides a quick, engaging, and fun understanding so that students can more easily understand mathematical concepts in flat-sided material. Virtual reality learning media has been extensively tested to be valid, practical, and suitable for use in learning. Suggestions for this research can provide an innovative development of virtual learning media, which still has many shortcomings, so that it is much better and produces like learning.